Welcome to My Trading Room, Volume I : Basics to Trading Global Shares, Futures, and Forex - Foundation of Trading. - Magliolo, Jacques (Business Expert Press, 2017)
This volume builds a foundation of knowledge in a comprehensive body of literature on trading to prepare the novice to become a professional trader. This volume starts with the total basics of trading with more in-depth knowledge being explored in the next two volumes.